2007
DOI: 10.1073/pnas.0706938104
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory and suppressive receptive field subunits in awake monkey primary visual cortex (V1)

Abstract: An essential step in understanding visual processing is to characterize the neuronal receptive fields (RFs) at each stage of the visual pathway. However, RF characterization beyond simple cells in the primary visual cortex (V1) remains a major challenge. Recent application of spike-triggered covariance (STC) analysis has greatly facilitated characterization of complex cell RFs in anesthetized animals. Here we apply STC to RF characterization in awake monkey V1. We found up to nine subunits for each cell, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 27 publications
3
76
1
Order By: Relevance
“…Our findings resemble recent receptive field modeling in primate primary visual cortex that revealed multiple STRFs for simple cells (40,41). Additionally, in both the visual and auditory systems, the structure of the nonlinearities varies with depth.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings resemble recent receptive field modeling in primate primary visual cortex that revealed multiple STRFs for simple cells (40,41). Additionally, in both the visual and auditory systems, the structure of the nonlinearities varies with depth.…”
Section: Discussionsupporting
confidence: 76%
“…2A, together with the spatial spectrum and associated nonlinear functions. Consistent with previous reports (20)(21)(22), we found that for most V1 neurons the RF contained multiple Gabor-like subunits of the same orientation ( Fig. 2A, cell 2), whereas a small number of them were unoriented with a single center/surround subunit (cell 1), similar to that found for lateral geniculate nucleus (LGN) neurons.…”
Section: Significancesupporting
confidence: 80%
“…Recent studies estimating such filters using reverse correlation methods suggest that macaque complex cells are better described with several additional filters Chen et al, 2007). In addition, Felsen et al (2005) showed that complex cells in cat V1 are tuned to the phase regularities of natural images.…”
Section: Importance Of Image Phase Structure For Perceptionmentioning
confidence: 99%